OCCUPATIONAL STRESS: THE IMPACT OF HEALTH OFFICIALS CALL CENTER IN THE REGION OF THE GREAT SÃO PAULO – BRAZIL (Fiep Bulletin - online, 2015)
The aim of this study is to evaluate the impact of workload on the prevalence of emotional imbalances, job satisfaction and quality of life of employees of the public service sector, (Call Center) in four companies of greater Sao Paulo. The study was conducted from August to December 2013 with descriptive, exploratory where 16 professionals were evaluated, four of the supervisory sector and 12 from the operational sector. Used two assessment instruments: QVS-80, to profile the subjects in personal areas, quality of life, work, health, lifestyle and family and the Stress Test for application in occupational environment whose goal is to assess the psychological aspects through numerical count. All subjects signed an Informed Consent Form (ICF), which were described items related to ethical aspects of research. The data collected showed the alarming statistics regarding the stress level of the subjects, where 25% are in a state of distress (state of exhaustion), presenting problems with depression and anxiety and negative feelings towards life, where everyone is in a psychiatric follow and three have been out of work, 57% have already been stress resistance, 100% experience pain in any region of the body and discomfort during the workday, where 75% are located in the cervical region; 89% nape practice any physical activity and 40% slept less than five hours per night. Data from this study show that will need to implement a program that can improve the quality of life of employees within the workplace, compliance with regulatory standards for breaks required by all employees, unsatisfactory data with respect to working conditions . It has been observed that employees who have double shifts exhibit a constant state of stress causing absenteeism and constant spacing.
Keywords: Occupational Stress; Work Environment; Workplace Exercise.